Kemudahan Biodegradasi Selulosa Bakteri dari Limbah Cucian Beras dengan Penambahan Gliserol, Kitosan, dan Nanopartikel Perak - Agung Nugaraha Catur Saputro; Baki Mulyani; Nanik Dwi Nurhayati; Yunita Kurniawan (Syarif Hidayatullah State Islamic University, 2016)
The objectives of this research were to study the effect of glycerol and chitosan addition toward biodegradability of cellulose based rice waste water, the effect of biodegradation time toward mass lost and biodegradability, and determine functional group and crystalinity of the highest biodegradability composite. Bacterial celluloses were prepared from 100 mL rice waste water that fermented by Acetobacter xylinum for 7 days with addition of glycerol (for Cellulose-Glycerol and Cellulose-Glycerol-Chitosan). Then, bacterial celluloses were immersed in chitosan solution (for Cellulose-Chitosan and Cellulose-Glycerol-Chitosan). The water in bacterial cellulose and its composites was removed by heating, then deposited silver nanoparticle on the bacterial cellulose and its composite. The silver nanoparticles were prepared by chemical reduction with using AgNO3 solution, trisodium citric as reducing agent, and gelatin as stabilizer. The silver nanoparticle was deposited into bacterial cellulose and its composites film by immersing method. After that, the bacterial cellulose and its composites were biodegradated by soil burrial test method for 14 days. Then, cellulose with the highest biodegradability was characterized by ATR-FTIR and XRD. The silver nanoparticle formation was showed by UV-Vis spectrum with peak in the 418.8 nm area. The glycerol addition can increase biodegradability, whereas the chitosan addition can decrease biodegradability. The increasing of biodegradation time, mass lost increased but the biodegradability decreased. After biodegradation, intensity of pyran cyclic in cellulose-glycerol which is deposited Ag (SG + Ag) decreased, but crystallinity of it increased. Keywords : Biodegradation, glycerol, chitosan, silver nanoparticle, bacterial cellulose. DOI: http://dx.doi.org/10.15408/jkv.v2i1.3111